Impact of acoustic waves on rainfall distribution in acoustics-induced artificial rainfall technology - Mengyao WANG; Jiaye LI; Ji CHEN; Jinzhao WANG; Songdong SHAO (Results in Engineering)
As a potentially effective method for increasing water resources, the acoustics-induced artificial rainfall technology has attracted wide attention due to being eco-friendly and low-cost. Despite recent advancements, the spatiotemporal characteristics and underlying mechanisms of acoustically induced rainfall remain insufficiently understood. In this study, a non-randomized acoustic rainfall field test was carried out in the Tibetan Plateau in 2020. Rainfall was measured by ground-based tipping-bucket rain gauges. Various classification criteria were applied to these rain gauges to analyze the acoustic impact on rainfall distribution. The results showed that the natural rainfall distribution is highly correlated with cloud conditions and terrain. The overall rainfall was more concentrated in the east. Under the influence of acoustic waves, the rainfall center shifted to the western region. The combined effect of the acoustic field and near-surface convection may cause this phenomenon. Compared with the natural rainfall process, the long-duration rainfall process under acoustic fields has an apparent two-stage pattern. The rainfall intensity is significantly higher in the central region (near the acoustic operation point) than on either side during the first stage. This phenomenon may be attributed to the triggering effect of acoustic waves on the formation process of large droplets. Rainfall in the second stage usually lasts for hours with random distribution, and the impact of acoustic waves may not be reflected in the rainfall distribution because of the complex cloud dynamics. These findings help fill the existing gap in understanding how artificial acoustic forcing interacts with precipitation processes over high-altitude regions.